THE CONTRADICTION of CERTAINTY and UNCERTAINTY in HEDGING and ITS IMPLICATIONS to LANGUAGE TEACHING - Nugroho, Aylanda (k@ta: A Biannual Publication on the Study of Language and Literature, 2004)
Hedging offers a contradiction in a way that it was “uncertain” words or phrases which in fact show certainty or accuracy. Second language learners need to learn to hedge appropriately in the second language in order not to sound rude or blunt.